Analysis of the influence of Competency, Independence, and Motivation on Audit Quality of the Tapin Regency Inspectorate - Melania, Melania; Kadir, Abdul; Amrulloh, Rifqi; Jayen, Fredy; Dewi, Riza Puspa (JURNAL APLIKASI PELAYARAN DAN KEPELABUHANAN, 2023)
Productive employees will have an impact on performance effectiveness which will be an added value for the Inspectorate. The importance of competence, independence, and high motivation that must be possessed by auditors has an impact on increasing the effectiveness of the performance of the Tapin Regency Inspectorate’s employees. This study aims to analyze and determine the partial influence of independence and motivational competence on the audit quality of the Tapin District Inspectorate, the simultaneous influence of independence competence and motivation on the audit quality of the Tapin District Inspectorate and the most dominant influence of competence, independence, and motivation on the audit quality of the Inspectorate. Tapin District. This research is correlation research with quantitative approach with total sampling technique. The subjects in this study were all 40 employees of the Tapin Regency Inspectorate. Data collection techniques using questionnaires, observation, and documentation. The types of data analysis used in this research are Instrument Test, Classical Assumption Test, Multiple Linear Regression Analysis, and Hypothetical Test with the help of the Statistical Package for The Social Sciences (SPSS) version 23.0 computer program. The results showed that there was a partially significant effect of Competence, Independence, and Motivation on the audit quality of the Tapin Regency Inspectorate, a simultaneous significant influence of Competence, Independence, and Motivation on the audit quality of the Tapin Regency Inspectorate and a dominantly significant influence of Independence on the audit quality of the Regency Inspectorate Tapin.